2016
DOI: 10.4025/actascianimsci.v38i3.31114
|View full text |Cite
|
Sign up to set email alerts
|

<b>Forage yield in pastures with bermuda grass mixed with different legumes

Abstract: Three grazing systems with Coastcross-1 bermuda grass (CC) + 100 kg N ha-1 year-1 + common vetch; CC + 100 kg N ha-1 year-1 + arrowleaf clover; and CC + 200 kg N ha-1 year-1 were evaluated. Thirteen grazing cycles were performed during the experimental period (313 days), with two, five, four and two cycles respectively in winter, spring, summer and fall. Lactating Holstein cows were used in the evaluation. Daily accumulation rate, forage production, rate of forage disappearance, agronomic intake, grazing effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Observing the plot of the curves representing the pastures under inoculation, it was observed that there is similarity, demonstrating, therefore, that there is no need to reinoculate the pasture. The daily accumulation rate recorded in the summer for inoculated pastures, of 66.8 kg ha -1 DM, is similar to that obtained by Anjos et al (2016) For the leaf blade: stem + sheath ratio of Coastcross-1 (Table 2), considering the same N levels, only in winter of the first year there was a difference (p ≤ 0.05) in pastures that received no nitrogen fertilization, with greater value when not inoculated. This behavior, although isolated, may be related to a possible greater development of the roots of inoculated plants, stimulated by the production of phytohormones, with consequently greater soil exploration, greater absorption of the N available (Moreira et al, 2010;Hungria et al, 2010) and, thus, greater shoot development, and proportionally of stems, as observed when N was applied.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Observing the plot of the curves representing the pastures under inoculation, it was observed that there is similarity, demonstrating, therefore, that there is no need to reinoculate the pasture. The daily accumulation rate recorded in the summer for inoculated pastures, of 66.8 kg ha -1 DM, is similar to that obtained by Anjos et al (2016) For the leaf blade: stem + sheath ratio of Coastcross-1 (Table 2), considering the same N levels, only in winter of the first year there was a difference (p ≤ 0.05) in pastures that received no nitrogen fertilization, with greater value when not inoculated. This behavior, although isolated, may be related to a possible greater development of the roots of inoculated plants, stimulated by the production of phytohormones, with consequently greater soil exploration, greater absorption of the N available (Moreira et al, 2010;Hungria et al, 2010) and, thus, greater shoot development, and proportionally of stems, as observed when N was applied.…”
Section: Resultssupporting
confidence: 67%
“…As for the distribution of forage yield throughout the year (Table 1), in general, it was in accordance with the production cycle of Coastcross-1 in subtropical regions, with higher yields in the summer, and lower in the spring and fall (Barbero et al, 2009;Aguirre et al, 2014;Anjos et al, 2016). Although, in the first year of evaluation, the climate had contributed to a cut in the winter, due to the milder temperatures, the production in this season was inferior to the others.…”
Section: Resultsmentioning
confidence: 60%
“…As for the other spontaneously growing species, the opposite trend was observed, revealing a linear descending trend as a function of N dosage. These species are usually less productive (Anjos et al, 2016) and less consumed by the animals (Olivo et al, 2014).…”
Section: Forage Massmentioning
confidence: 99%